RANCANGAN PEMBELAJARAN ILMU TAJWID BERBASIS MULTI MEDIA UNTUK SISWA TINGKAT DASAR PADA TAMAN PENDIDIKAN AL-QUR’AN DTA AT-TAQWA - FINTRI Indriyani (Paradigma, 2015)
Understanding of religion should be done by parents from since childhood, at which time the child can easily absorb knowledge, but how that is done to convey that knowledge should be done with the right method to facilitate the child understand. The method has been used in Islamic religious learning in particular subjects, al-Qur'an in Al-Qur'an garden diniyah education, ta'miliyah and awaliyah (DTA) at-Taqwa is a writer doing research lecture method, the learning method less attractive for the students, so that the level of their understanding of the material is less, it can be seen from the daily repetition of the material al-Qur'an student base level DTA is lower compared to other subject matter. To overcome these problems, needed a fun but learning methods can be understood easily. In this case we can use interactive multimedia. Learning with interactive multimedia, is expected to improve students' learning motivation, increase comprehension faster than just read, can facilitate the process of learning and teaching activities at the Garden Education Qur'an diniyah, ta'miliyah, awaliyah (DTA) At-Taqwa . Learning with multimedia applications using already testing by whitebox and black box testing, the test results can be concluded that the system that has made the program is already running in accordance with the purpose of planning.